Specification and design of distributed hard real-time systems - Roberto, Paulo [UNESP]; Tepedino, Pierri [UNESP]; Kimer, Tereza Gonçalves (Institute of Electrical and Electronics Engineers (IEEE), 1995)
This paper presents an integrated approach for specification and design of software for distributed hard real-time systems. The approach adopts a graph-based model, combined with a pre-run-time scheduling. This gives important features to the approach, making {possible the solution of crucial questions along the development of these systems.
Keywords: Design; Distributed systems; Real-time systems; Requirements specification